Dominance and toxicity without lethality: Exploring biomass, cyanometabolites, and Daphnia responses across Cyanobacterial strains - Wejnerowski, Łukasz; Dulić, Tamara; Akter, Sultana; Rybak, Michał; Piasecka, Agnieszka; Szymkowiak, Jakub; Kamiński, Oskar; Czerepska, Anna; Pniewski, Filip; Svirčev, Zorica; Poniecka, Ewa; Zawierucha, Krzysztof; et al. (Wiley, 2026)
Cyanobacteria are cosmopolitan, important components of biomass with a remarkable ability to synthesize a diverse array of bioactive compounds, some of which may have toxic effects on other organisms and ecosystems. In this study, filamentous cyanobacterial strains isolated predominantly from temperate European freshwaters (Aphanizomenon, Chrysosporum, Cuspidothrix, Dolichospermum, Planktothrix, Raphidiopsis), with a subset from Arctic waters (Microcoleus, Phormidesmis), were qualitatively screened for commonly studied cyanometabolites, using immunoassays and chromatographic techniques. We also assessed the effects of culture extracts and filtrates on the survival of Daphnia magna and Daphnia pulicaria. The results indicated a broad capacity among tested strains to produce toxic and bioactive compounds. Specifically, we detected anabaenopeptins, anatoxin-a, cylindrospermopsin, microcystins, and saxitoxins. Although numerous strains showed the potential to produce a variety of toxic and bioactive compounds and reached high biomass after 40 days of incubation, their extracts and filtrates frequently had negligible negative effects on the survival of Daphnia. In contrast, significant lethality was observed in response to planktic Limnothrix sp. and glacial Microcoelus autumnalis that tested negative for the studied compounds, as well as for an Aphanizomenon klebahnii strain in which only anabaenopeptins were detected. We also observed a positive relationship between the biomass used to prepare cyanobacterial extracts and Daphnia survival, and this result raises the question of whether there is a trade-off between the growth rates of strains and their toxicities. Our study extends the current knowledge of the geographical distribution of toxic cyanobacteria and suggests that some of them may also produce other, yet unidentified toxic compounds.